Reconstruction of the coronoid process with the olecranon tip for chronic elbow dislocation in children: A rare case report and literature review - Jiang, Yikun; Qi, Le; Peng, Chuangang; Li, Qiwei; Zhang, Peng; Wang, Yanbing; Wu, Dankai (Frontiers in Pediatrics, 2022)
The coronoid process of the ulna, as a key part of the elbow joint, plays an important role in maintaining elbow joint stability. Reconstruction of the coronoid process is necessary in both acute and chronic coronoid defects to restore elbow stability and avoid early joint degeneration. The olecranon tip may be a useful autologous osteochondral graft for reconstructing the same shape of the ulna coronoid process. The purpose of this report was to verify if reconstruction of the coronoid process with the olecranon tip can restore elbow stability and kinematics. Here, we report a 13-year-old boy who had undergone Kirschner-wire fixation for a left supracondylar fracture of the left humerus 9 years previously. After that, the right elbow dislocation and varus deformity gradually appeared. Imaging revealed posterolateral dislocation of the left elbow due to the absence of the coronoid process of the ulna. We reconstructed the ulnar coronoid process by intercepting the ipsilateral olecranon tip. After 22 months of follow-up, the range of motion of the left elbow joint was normal, and the cubitus varus deformity disappeared. The results of this report suggest that olecranon tip autografts are suitable to replace transverse coronoid defects. Given the patient's satisfactory clinical results, this reconstruction technique is safe and effective for the treatment of chronic elbow instability due to coronoid process defects of the ulna.